PENGARUH PROFITABILTAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN JASA SUB SEKTOR TRANSPORTASI PERIODE 2018-2022 - Fahira, Andi Nurul; Nurwahyuni, Nurwahyuni; Ikhtiari, Kirana (Jurnal Akuntansi, 2024)
This study aims to assess the impact of profitability and liquidity ratios on firm value within the transportation service sector. The research adopts a quantitative approach, utilizing secondary data sourced from financial reports obtained from https://www.idx.co.id/id and official company websites. The study focuses on transportation companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022, with a purposive sample size of 135 data points. The analytical method employed is multiple linear regression analysis. The findings suggest that profitability ratios, tested through hypothesis testing, exhibit a positive but statistically insignificant influence on firm value. This implies that changes in profitability ratios, whether positive or negative, do not significantly affect firm value. Conversely, liquidity ratios demonstrate a positive and statistically significant impact on firm value, indicating that variations in liquidity ratios do influence firm value. In conclusion, the study indicates that while profitability ratios do not exert a significant influence on firm value in the transportation sector, liquidity ratios are instrumental in shaping firm value.